Efektifitas Komunikasi Pemasaran Bisnis UMKM Melalui Fitur Reels Instagram - Nandhita Ahsanul Hawa; Budi Harto; Panji Pramuditha (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
An online platform known as social media enables direct or indirect business engagement and promotion. The increasing growth of internet users has sped up information flow and made it simpler for users to communicate with one another across time, space, and distance. Researchers conduct their research using qualitative approaches, which rely on information gleaned from questionnaire distribution, observations, and interview findings. According to survey findings, 89% of MSMEs are happy with the way Instagram is being used to communicate and sell their businesses. Instagram reelss are a great tool for MSME businesses since they advertise establishments that Instagram users can view. MSMEs concur that the brand image of products on Instagram is excellent since devoted customers with great Instagram profiles will stick with the company. MSMEs who use Instagram for social media are successful marketers who gain a competitive edge in this way